"Japan is back": Autonomy and balancing amidst an unstable China–U.S.–Japan triangle. Issue 2 (1st May 2018) - Fatton, Lionel P.
Abstract: Japan's security policy has changed dramatically in recent years. The country balances harder against China, and its armed forces are increasingly autonomous from their American counterparts. What explains Japan's growing autonomy and balancing tendency after decades of relative apathy? I argue that this new strategic orientation results from unprecedented doubts about the effectiveness of its traditional security policy amidst an unstable China–U.S.–Japan triangular relationship. Tokyo is increasingly uncertain about American security commitments in the face of a more assertive China. As both the alliance with the United States and the accommodation of China are becoming unsuitable strategies for guaranteeing national security, Japan reverts to a more autonomous and resolute posture. Japan's new security policy will have important consequences for the triangular relationship.